The Business Permits in Gampong Beurawe Aceh: The Existence of the Current Aceh Qanun: Izin Usaha di Gampong Beurawe Aceh: Eksistensi Qanun Aceh saat ini - Widoretno Putri, Citraresmi (Rechtsidee, 2022)
The purpose of this study is to examine the existence of Qanun related to the issuance of business licenses regarding government entertainment and games in Gampong Regulations. in Gampong Beurawe in the city of Banda Aceh related to Islamic principles. The research method is normative law by using a statutory-regulatory approach and a comparative approach. It was found that the Province of Nanggroe Aceh Darussalam with Islamic law was able to change a concept of behavioral power that had grown self-awareness through religious norms into a concept of behavioral power that could be imposed from outside humans with legal norms in the form of Qanun which were equivalent to Regional Regulations. This gave birth to Gampong Beurawe as Gampong Syariah. Law Number 11 of 2020 to Government Regulation of the Republic of Indonesia Number 6 of 2021 is one of the supervisory systems from the center for regions related to the issuance of business permits in the Regions electronically. The existence of government regulations makes it easier to control business licensing that is not in accordance with the concept of Islamic law and practices related to other licensing.